A paradigm of care - Stake, Robert E.; Visse, Merel, 1972- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
Remember the pots hammered by spoons from high Manhattan windows, and parades of cars and pick-up trucks holding dear the medical professionals responding to covid-19. This book is part of that chorus, that march, to express appreciation for the giving of care. And beyond doctors and nurses, bless their hearts, to mothers caring for their babies, for captains for their teams, for the soon-to-be widowers for their wives and teachers for their students, but also for the ranchers for their cattle and the contemplative world for our environment. This is a book to think more closely of the support for care, individual as it so often will be, to be woven more closely together in a paradigm of care.Care is always prominent. Care for others, of the family, care for those of the tribe, care for animals and homes and gardens and properties, self-care. And the purse. Even without teaching, compensation, or legislation, care survives, but even with these helpings, it falls short of the need. We live in a crisis of care. Thinking explicitly and beyond health care. There is no mechanism of state and conscience that delivers care to all the venues of need, and seldom in the amounts needed. The reservoirs of care are far from empty, but at a mark that needs topping up. There is need for care advocacy, a care ethic, a paradigm. This book is about that paradigm.A care paradigm may bring comfort and recovery more fully to the people and organic creations of the world. The paradigm hears the moan of indifference. It draws upon the eyes of the heart. The paradigm is about how we see the need for care. The care paradigm, the grand beholding, is manifest in how we provide for others, how we nurture them, give succor, how we are disposed, and are not, to sacrifice to relieve their hurt. It is not only caring for those visibly needing care, unable to care for themselves, but caring for all. It is having a disposition that the hurts, large and small, that all of us carry, arouse concern and appreciation from and for each individual, the community and the world.